Resilience and stigma among children with HIV, tuberculosis, and stunting: A literature review - Najmah Najmah; Ajeng Fathia Nurqanita; Ullya Fitri Samsuri; Sasyi Friska Nindiyanti; Marieska Verawaty; Iwan Stiabudi; Sari Andajani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Health-related stigma is a social phenomenon closely linked to inequality and marginalization. Children living with HIV, tuberculosis (TB), and stunting are particularly vulnerable to intersecting forms of stigma, including discrimination related to illness, poverty, and family background. These overlapping stigmas often restrict social participation, affect mental well-being, and hinder access to health services, thereby reinforcing cycles of vulnerability. Purpose: This literature review aims to synthesize existing evidence on the manifestations of stigma and resilience among children affected by HIV, TB, and stunting within the Indonesian and broader Asian contexts. Method: A literature review was conducted using databases including Google Scholar, PubMed, and ScienceDirect. Articles published between 2019 and 2024 were screened based on predefined inclusion criteria. Eighteen relevant studies were selected and analyzed using a thematic approach to identify recurring patterns related to stigma and resilience. Results: The findings indicate that stigma operates across multiple levels. At the intrapersonal level, caregivers often experience self-stigma, shame, and psychological distress, which negatively influence health-seeking behaviors. At the interpersonal level, children encounter social exclusion, peer discrimination, and community stigma that reduce their quality of life. At the structural level, stigmatizing attitudes among some health workers and discriminatory practices within health systems create barriers to equitable care. These forms of stigma are frequently intensified by socioeconomic factors such as poverty and limited educational access. Conclusion: Stigma affecting children with HIV, TB, and stunting is a multi-dimensional issue shaped by personal, social, and structural determinants. Addressing this problem requires comprehensive strategies, including community education, strengthening family and social support, and ensuring that health services are delivered in a non-discriminatory and child-centered manner.